(untitled) (Journal of Social Sciences Review, 2025)
The aim of the study is to investigate the impact of work-related stress on workplace performance. By determining and justifying the relationship between Emotional Exhaustion and Goal-focused leader behavior (i.e., supervisory performance is one of the key factors in achieving organizational goals), this research study aims to expand the literature regarding the interaction between Emotional Exhaustion and workplace performance that leads to organizational goals. To implement organizational goals strategically, leaders who are goal-focused communicate and convey the goals of the organization and support employees’ efforts to achieve them. Hypothesizing bottom-line mentality also plays an important mediating role in explaining why there is a relationship between Emotional Exhaustion and Goal-focused leader behavior (GFLB). It is investigated the moderating role of Obsessive Passion between the relationship of Emotional Exhaustion and Bottom-line mentality of supervisors. It is also investigated the moderating role of Perceived Organizational Support between the relationship of Bottom-line mentality of supervisors and Goal-focused leader behavior. This study examined the relationship between these variables based on the data collected by front-line managers in the banking sector in Punjab, Pakistan. Data was analyzed using SPSS version 27 and Smart-PLS (version-4) to determine how variables influence each other. Using a one-shot survey method and face-to-face interviews, this study collected data. Through PLS-SEM, the study considered the relationship between the proposed theoretical model and 402 valid research questionnaires. Using validity and reliability measurements, the path model fits well with the quantitative data. Consequently, all hypotheses are accepted. Study has theoretical as well as practical contributions.